Study English IELTS preparation : resource book - Larbalestier; Shymkiw (Insearch Limited and ABC Asia Pacific, 2005)
This truly unique program was developed by Insearch UTS and ABC Asia Pacific and has been broadcast throughout the Asian Pacific region. Consisting of 26 ten-minute episodes based on authentic footage, each episode focuses on a language element of par